Penerapan Metode Modified Distribution dengan Metode Vogel’s Approximation Sebagai Solusi Awal Pada Optimasi Biaya Transportasi UD Salim Abadi Lampung - Cahyanti, Alfiana; Helma, Helma (UNIVERSITAS NEGERI PADANG, 2024)
Transportation problems are common issues faced by companies in the goods delivery process. UD Salim Abadi Lampung is a company engaged in marketing agricultural products. The company operates three central warehouses and seven branch warehouses, with annual transportation costs amounting to Rp. 357,184,000. The purpose of this research is to determine the optimal transportation cost, develop a transportation model, and ascertain the quantity of supplied goods. The method used is the Modified Distribution (MODI) method, with Vogel’s Approximation Method (VAM) as the initial solution. Both methods are part of the transportation method used to solve transportation problems. In this research, using VAM as an initial solution resulted in a cost of Rp. 343,334,786.5, while the MODI method, used for the optimal solution, resulted in a cost of Rp. 327,066,161.4. Therefore, based on the optimal solution, UD Salim Abadi Lampung can save Rp. 30,117,838.60 in annual transportation costs for distributing goods.Keyword : Transportation Cost Optimization, Transportation Method, Vogel’s Approximation Method, Modified Distribution Method